Strengthening and reconstruction of drilling core pipe for engineering and geological exploration - Dzyubyk, Andrij; Dzyubyk, Liudmyla; Shpak, Bohdan (Видавництво Львівської політехніки, 2022)
Currently, there is a tendency to increase the depth of gaseous and liquid fossils extraction. Therefore, prospecting and developing new deposits is promising. There is also a need to create new freshwater sources and implement relevant geological work based on this need. It is essential to have information about the characteristics of the explored slabs and the geology of the fields in general. Implementation of engineering and geological core drilling exploration is the most acceptable and provides the necessary data. Here, the peculiarities of the technological schemes of the process implementation make it possible to obtain separate sections of structures at a depth of the drilling equipment. It is essential to use traditional equipment, recommended for decades and provides the necessary results [1–3]. In the drilling process, you can achieve different diameters and depths of wells execution, obtain fossil samples etc. Engineering and geological exploration drilling is now taking on increased use in various industries [3]. Therefore, the problem of providing highquality drilling tools, the stability of their operating characteristics, and the possibility of usage in different conditions is an urgent need today. Modern drilling problems determine the usage of components of the core set with the appropriate physical and mechanical characteristics. Especially it relates to elements close to the drilling tool and the place of fossil; destruction – drill pipe. It is installed immediately after the crown core drill and receives almost the same loads and effects during working [1–3]. Conditions for the implementation of the process of core drilling are characterized primarily by the effect on the elements of the significant axial and twisted core set forces. There is the influence of the corrosive and active environment of the fossil in the washing and lubricating liquids well, etc. High temperatures are also observed at the drilling sites [3], which negatively affect the working tool and speed up its operation. As a result, there is an intensive shock, and abrasive core pipe wear and operation indicators change their constructive size. As a result, it is necessary to replace the operated drill string periodically. Considering modern technical and economic factors, it may be decided to repair a pipe to its original size in many cases. There are tasks for providing the appropriate characteristics of the core pipe surface. It is possible to model such properties of the new surface that functionally the best meet the conditions of the drilling process of a given geological formation. The peculiarities of applying the therapeutic layer on the surface of the core pipe are investigated in work. The experience shows that using electric arc surfacing under the flux layer is expedient. This provides the necessary adhesion of the applied layer and promotes obtaining resistance to the operation surface of the core pipe. At the same time, there is high-quality protection and the possibility of additional alloying through the flux-slaggy welding bath. Using electrode powder type wires creates conditions for flexibility to achieve the established characteristics of functional layers [4–6]. The filling flux, located in the cross-section of the electrode wire, can be easily changed by chemical composition. At the same time, it is possible to make relatively small parties of a wire with the set characteristics. The technological scheme justification about the core pipe surfacing is performed. It provides the previous displacement of the electrode butt size from the zenith of the core pipe to prevent the welding bath from spreading. The structural pipe size , the requirements for residual deformations, and the conditions of shapping the welded layer show the practicality of welding on a helix.
Keywords: core pipe; geological and engineering prospecting; electric arc surfacing; running welding energy; electrode flux-cored wires; wear-resistant coatings; thermal impact zone; heating for surfacing; hardening structures; welding bath